How does pain lead to disability? A systematic review and meta-analysis of mediation studies in people with back and neck pain - Lee, Hopin; Hübscher, Markus; Moseley, G Lorimer; Kamper, Steven J; Traeger, Adrian C; Mansell, Gemma; McAuley, James H (Pain (Amsterdam), 2015)
Disability is an important outcome from a clinical and public health perspective. However, it is unclear how disability develops in people with low back pain or neck pain. More specifically, the mechanisms by which pain leads to disability are not well understood. Mediation analysis is a way of investigating these mechanisms by examining the extent to which an intermediate variable explains the effect of an exposure on an outcome. This systematic review and meta-analysis aimed to identify and examine the extent to which putative mediators explain the effect of pain on disability in people with low back pain or neck pain. Five electronic databases were searched. We found 12 studies (N = 2961) that examined how pain leads to disability with mediation analysis. Standardized regression coefficients (β) of the indirect and total paths were pooled. We found evidence to show that self-efficacy (β = 0.23, 95% confidence interval [CI] = 0.10 to 0.34), psychological distress (β = 0.10, 95% CI = 0.01 to 0.18), and fear (β = 0.08, 95% CI = 0.01 to 0.14) mediated the relationship between pain and disability, but catastrophizing did not (β = 0.07, 95% CI = -0.06 to 0.19). The methodological quality of these studies was low, and we highlight potential areas for development. Nonetheless, the results suggest that there are significant mediating effects of self-efficacy, psychological distress, and fear, which underpins the direct targeting of these constructs in treatment.